2022
DOI: 10.3390/vaccines10070999
|View full text |Cite
|
Sign up to set email alerts
|

Stability Program in Dendritic Cell Vaccines: A “Real-World” Experience in the Immuno-Gene Therapy Factory of Romagna Cancer Center

Abstract: Advanced therapy medical products (ATMPs) are rapidly growing as innovative medicines for the treatment of several diseases. Hence, the role of quality analytical tests to ensure consistent product safety and quality has become highly relevant. Several clinical trials involving dendritic cell (DC)-based vaccines for cancer treatment are ongoing at our institute. The DC-based vaccine is prepared via CD14+ monocyte differentiation. A fresh dose of 10 million DCs is administered to the patient, while the remainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Viability is one mandatory quality control of GMP-grade therapeutic DCs (39). In the present work we have found that although viability appears very high shortly after human cDC isolation, subsequent spontaneous apoptosis may be extensive following short-term culture.…”
Section: Discussionmentioning
confidence: 51%
“…Viability is one mandatory quality control of GMP-grade therapeutic DCs (39). In the present work we have found that although viability appears very high shortly after human cDC isolation, subsequent spontaneous apoptosis may be extensive following short-term culture.…”
Section: Discussionmentioning
confidence: 51%
“…Another strategy involves utilizing autologous dendritic cells activated through exposure to tumor-associated antigens, along with enhancing the cellular response through exposure to adjuvant molecules (see Figure 2 ) [ 6 , 7 ]. Dendritic cells, serving as antigen-presenting cells, are inoculated autologously and activated, mirroring the approach seen with Sipuleucel-T, an approved therapy for metastatic prostate cancer [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It can regulate the innate and adaptive immune responses of patients through activating and resistance. These characteristics make them playing a central role in regulating the immune response and have been widely used in the clinical application of cancer [10]. Many researchers are committed to the exploration of DC cancer therapeutic vaccine, and many relevant reports have appeared as early as 1999 [11].…”
Section: Introductionmentioning
confidence: 99%